PENGARUH PERMAINAN TRADISIONAL ENGKLEK TERHADAP PEMBELAJARAN SISWA KELAS IV SDN BLULUK I LAMONGAN - Adinda Amelia Anugerah Putri; Afakhrul Masub Bakhtiar (STKIP Subang, 2022)
Abstract This study aims to determine the effect of the traditional engklek game on improving the learning of fourth grade students of SDN Bluluk I Lamongan. One of the problems of education is the lack of media facilities and infrastructure, so teachers are required to be creative in improving the quality of learning in the classroom, such as developing learning media in the classroom. One of the interesting learning media that can overcome student boredom in learning activities is game-based learning activities, such as the application of the traditional engklek game media. The research method used is a quasi-experimental method. The quasi -experimental method is a research method used to find the effect of certain treatments. To obtain data in accordance with the purpose of this study, using experiments, namely by giving treatment to students in the form of pre-test activities, treatment or exercises and final tests. From the learning outcomes of fourth grade students of SDN Bluluk I Lamongan with the traditional engklek game media, it can be concluded that the media can improve the student learning process and increase students' enthusiasm after using the engklek traditional game media and the use of learning media in learning activities makes it easier for students to gain understanding and motivate students to learn so as to get good learning outcomes and learning outcomes increase. Keywords : Traditional Englek Game, Learning.